Outline of a Serbian Orthodox Doctrine of Righteous War - Emil Hilton Saggau (Religions)
The post-communist period has seen several wars in regions with a majority of Eastern Orthodox Christians. These conflicts have prompted Eastern Orthodox churches to formulate stances on war and develop new doctrines of righteous war. These responses draw on a long lineage of Eastern Roman and Slavonic traditions, particularly the Cyrillian doctrine of righteous war expounded in the Life of Constantine-Cyril. This paper examines the theological responses of the Serbian Orthodox Church to the wars in the former Yugoslavia, providing a reference point for comparison with the current theological debates and assessment of doctrines of warfare in light of the war in Ukraine. The focus is on the biblical hermeneutics and theological framing of various Serbian-centered doctrines. These new outlines draw on diverse traditions within Slavonic and Eastern Orthodox theology. The paper aims to provide insights into the shaping of Eastern Orthodox positions on war and the theological genesis of justifications for war. The discussion sheds light on the intricate relationship between war and Christianity within the Eastern Orthodox context in Serbia.